Astragalus depressus L. in Romania. Chorology with new localities - Bartok, Attila; Lazar, Gabriel; Indreica, Adrian (Universitatea A.I. Cuza, Iasi, 2014)
The paper points one new locality in Transylvania (Romania) of Astragalus depressus L. and one new locality in Oltenia, tracking at the same time the species distribution in Romania, using herbarium materials and existing bibliographic sources
Keywords: Astragalus depressus L.; threatened species; chorology; Carpathians